Dosen Kopertis Wilayah I Dpk. FKIP UISU Medan Jl. Sisingamangaraja Medan - Deliani, Hj. (Universitas Islam Sumatera Utara, 2013)
ABSTRACT Character education based on basic human character from the universal moral which is based onreligious values that are considered as âThe Golden Ruleâ. Character education can have definitegoals when based on the core values of love of God and his creation, responsibility, honesty,respect and courtesy, compassion, caring and cooperation, confidence, creativity, hard work andperseverance, justice and leadership, good and humble, peace-loving, tolerance and love of unity. Nowadays many people are demanding an increase in the intensity and quality of implementationof character education in the formal education institution, these claims are based on a growingsocial phenomenon, namely the rising juvenile delinquency in society, such as a mass brawl and avariety of other cases of moral decadence. Even in some big cities, such symptoms has reached theextent that disturbing. Therefore the formal educational institutions as the official youth coachingcontainers is expected to boost its role in shaping the personality of teenagers through an increasein the intensity and quality of character education. Keywords : character education, formal education institution, moral, personality, teenagers.